The Relationship Between Linguistic Intelligence and Social Interaction of Buddhist Young People: A Perspective on Buddhist Education - Prinyana Putra; Sidartha Adi Gautama; Vike Aprilianin Marwintaria sap; Iin Avitasari; Wistina Seneru; Karsinah Karsinah; Widiyanto Widiyanto; Eko Pramono (Universitas Sebelas Maret, 2024)
The purpose of this study was to find out how linguistic intelligence relates to social interaction between young men and women in monasteries from the point of view of Buddhist education. The problems that occur in students are difficulty in expressing opinions, lack of vocabulary that inhibits good self-expression, misunderstandings in communication, and lack of consistent practice, which can reduce language skills. Linguistic A person's ability to use language effectively, both in writing and speaking, is known as intelligence, including the ability to understand, interpret, and express ideas or information clearly and accurately. Social interaction is a relationship or communication between two or more people who talk or do something that has an impact on each other. This can be a conversation, cooperation, or other everyday actions involving other people. This research is classified as a correlational research that uses a quantitative approach. The population of this study was the Buddhist Youth in one of Buddhist Temple in West Jakarta, totaling 30 respondents. The respondents used for the instrument trial in this study were 30 respondents Based on the results of data analysis, it can be concluded that among the Vihara youth there is a relationship between each other and social interaction, with a relationship magnitude value of 0.834 and a significance level of 0.000 at the extreme level.